(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
This article aims to investigate two novels of Toni Morrison, Beloved and The Bluest Eye, by a cultural materialistic approach. Cultural materialists emphasize on the cultural aspects and elements of literary texts. They study issues such as race, gender, sexuality, social class, and slavery. In other words, they put under investigation the marginalized people of society, like black people, females, and slaves. In this regard, Toni Morrison is a great writer whose writings are replete with cultural issues. As most of the main characters of Toni Morrison’s novels are black people, so it can be concluded that for her, marginalized people of society and minorities especially females, are at center. Therefore, in this paper, it is aimed to emphasize on cultural elements of Morrison’s novels, Beloved and The Bluest Eye, and determine what stance she takes toward such minorities.